The effectiveness of business capital assistance to asnaf entrepreneurs: a study in Maim, Malacca - Abang Abai, Dayang Shobihah; Awang, Mohd Daud; Latip, Malisah; Hamli, Hadi (Human Resources Management Academic Research Society (HRMARS), 2023)
The zakat institution provides business capital aid to enhance the living standards of asnaf entrepreneurs and encourage their transition to entrepreneurship and zakat contributors.The aim of study to assess the extent to which the Malacca Islamic Religious Council plays a new strategy for zakat distribution in developing the economy of Asnaf Entrepreneurs.This study uses a qualitative research design through interview procedures and document evaluation. The study results show that the research conducted is satisfactory and answers every researcher's question. The theme that emerged from the first question was the form of capital assistance, financial assistance and equipment assistance. Researchers hope that the findings of this study can provide useful information to zakat institutions to further improve the efficiency of zakat distribution to the poor in this country.